2014
DOI: 10.4049/jimmunol.1400434
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylation Critically Determines T Cell Subset Radiosensitivity

Abstract: Lymphocytes are sensitive to ionizing radiation and naïve lymphocytes are more radiosensitive than their memory counterparts. Less is known about radiosensitivity of memory cell subsets. We examined the radiosensitivity of naïve (TN), effector memory (TEM), and central memory (TCM) T cell subsets in C57BL/6 mice, and found TEM to be more resistant to radiation-induced apoptosis than either TN or TCM. Surprisingly, we found no correlation between the extent of radiation-induced apoptosis in T cell subsets and :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…According to our findings, the observed differences in foci 24 h postirradiation and micronuclei yields between newborn and adult T lymphocytes are related to the immunophenotypic changes in T-lymphocyte composition with respect to naive and memory subsets. In agreement with our findings, studies in murine models could also show that naive lymphocytes are more radiosensitive than their memory counterparts (57)(58)(59). Up to now, the underlying mechanisms of the observed difference in radiosensitivity of human naive and memory T-lymphocyte subsets remains an open question and future research is warranted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to our findings, the observed differences in foci 24 h postirradiation and micronuclei yields between newborn and adult T lymphocytes are related to the immunophenotypic changes in T-lymphocyte composition with respect to naive and memory subsets. In agreement with our findings, studies in murine models could also show that naive lymphocytes are more radiosensitive than their memory counterparts (57)(58)(59). Up to now, the underlying mechanisms of the observed difference in radiosensitivity of human naive and memory T-lymphocyte subsets remains an open question and future research is warranted.…”
Section: Discussionsupporting
confidence: 90%
“…The memory CD4 þ T-cell subset in infants and young children has a significantly higher ratio of central memory to effector memory CD4 T cells than in adults (69). The murine study of Pugh et al demonstrated a difference in radiosensitivity between these memory subsets, which was again linked to their chromatin state (57). Although no statistically significant difference could be observed in residual foci and micronuclei levels of newborn and adult memory CD4 þ subsets, the P values were less convincing (P ¼ 0.150) than those we obtained for the naive cells and this can probably be attributed to the T lymphocyte central to effector memory cell ratio.…”
Section: Discussionmentioning
confidence: 99%
“…54,59 Also, chromatin structure varies with cell activity and status, and this variation is a suggested explanation for observed differences in radiosensitivity between T-cell subsets. 60 In the longer term, greater understanding of the dynamics of RIF viz-a-viz chromatin structure should give rise to new biomarkers of radiosensitivity and identify novel therapeutic targets.…”
Section: Chromatin Structure and Targetingmentioning
confidence: 99%
“…Interestingly, we showed a slight depletion of RTEs in patients after local non-mediastinal RT. Such effect after peripheral local irradiation was also described by several authors [15,19] and may be explained by higher sensitivity of naïve T cells to RT compared with memory T-cells [20]. Yovino et al recently demonstrated that 61.5% of the blood pool received more than 0.5 Gy after local irradiation in total dose of 20 Gy [19], wherein the dose required to reduce the surviving fraction of T cells to 50% is about 2 Gy [21].…”
Section: Discussionmentioning
confidence: 86%